The Ciceronian Book and its Influence: A Statistical Approach - Stover, Justin (Ciceroniana On Line, 2021)
The length of books in the era of the bookroll has never received more than sporadic attention. Using electronic counting methods, this study constructs statistical models of the Ciceronian book in three different genres, rhetoric, philosophy, and epistolography, and argues that Cicero’s literary production marks an inflection point in the development of the Roman literary book, and whose book-model would influence literary production down to the age of Apuleius and Gellius.